Female Pioneers from Ancient Egypt and the Middle East
XII, 203 p. 38 illus., 23 illus. in color.
Keywords: This book explores the contributions of Eastern female pioneers in science, politics and arts from Ancient Egypt to modern times, and discusses the possible psychological and social impact of this knowledge on today’s gender role in Eastern and Western Societies. Based on psychological studies on social learning, the book argues that profound knowledge of the historical contributions of Eastern female pioneers in science, politics and arts can improve today’s gender roles in Middle Eastern countries and inspire young women living in Western Societies with Eastern migration background. Spanning disciplines such as Natural sciences, Neuroscience, Psychology, Sociology, Islamic Theology, History and Arts, and including contributions from diverse geographical regions across the world, this book provides an elaborate review of the gender role of women in Ancient Egypt and the Middle East, outlining their prominence and influence and discusses the possible psychological and social impact of this knowledge on today’s gender roles. .